The efficacy of a structured group therapy intervention in improving communication and coping skills for adult cochlear implant recipients. - Heydebrand G; Mauze E; Tye-Murray N; Binzer S; Skinner M (International Journal of Audiology, 2005)
This paper reports on an evaluation of a structured group therapy intervention for adult cochlear implant (CI) recipients designed to improve overall communication and coping skills. 33 adult CI recipients (14 males, 19 females; mean age 61; 1-14 years since Cl) participated in a 2-day structured group therapy intervention with a follow-up session 4 weeks later. Measures were: communication behaviors (CPHI), assertiveness (Rathus), depression (DASS), and behavior during conversation (Dyalog). TCI personality traits were utilized as predictors of change. Repeated measures analyses showed that participants demonstrated significant improvements on measures of assertiveness, emotional well-being, and coping behaviors at 3 months post-intervention that persisted at a 12-month follow-up. Several personality traits predicted change. Although subjects had presumably adapted to their cochlear implants and had learned communication strategies in hearing rehabilitation programs, the improvements on several measures suggest that a structured group therapy intervention can enhance outcome following cochlear implantation.